2008
DOI: 10.1002/jez.461
|View full text |Cite
|
Sign up to set email alerts
|

Acute cold‐ and chronic heat‐exposure upregulate hepatic leptin and muscle uncoupling protein (UCP) gene expression in broiler chickens

Abstract: Emerging evidence showed that variations in environmental temperature affect both leptin and uncoupling protein (UCP) gene expression in mammals, whereas a little is known about such interactions in birds. Thus, we conducted the present study to investigate the influence of acute (2 hours) cold (4 degrees C) and chronic (10 days) heat (32 degrees C) exposure on hepatic leptin and muscle UCP gene expression in 5-wk-old broiler chickens. Both cold- and heat-exposure significantly (P < 0.05 to P < 0.001) upregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 61 publications
2
19
1
1
Order By: Relevance
“…This is consistent with earlier studies (Dridi et al, 2004) and suggests that UCP may affect animal performance by increasing energy dissipation by mitochondrial oxidation. Contrary to published findings, in which several studies showed that UCP mRNA expression may change as a function of environmental temperature (Toyomizu et al, 2002;Dridi et al, 2008), we did not observe any environmental effect on UCP mRNA expression.…”
Section: Discussioncontrasting
confidence: 87%
“…This is consistent with earlier studies (Dridi et al, 2004) and suggests that UCP may affect animal performance by increasing energy dissipation by mitochondrial oxidation. Contrary to published findings, in which several studies showed that UCP mRNA expression may change as a function of environmental temperature (Toyomizu et al, 2002;Dridi et al, 2008), we did not observe any environmental effect on UCP mRNA expression.…”
Section: Discussioncontrasting
confidence: 87%
“…This finding is partially in agreement with the reports in humans, in which cold exposure increases circulating irisin levels, possibly associated with shivering-related muscle contraction and augmentation of brown fat-like thermogenesis (Lee et al, 2014). In birds, owing to lack of the brown adipose tissue (BAT) for heat production, thus, skeletal muscle is an important source of thermogenesis for body to counter cold (Dridi et al, 2008;Raimbault et al, 2001;Toyomizu et al, 2002;Ueda et al, 2005). Of the multiple factors involved in cold-induced thermogenesis, avian uncoupling protein homolog (avUCP) and PPARγ co-activator-1ɑ (avPGC1-ɑ) in chicken muscle can be induced by cold (Raimbault et al, 2001;Ueda et al, 2005), and thus are suggested to play critical roles in cold-induced adaptive thermogenesis and muscle fiber type conversion (Ueda et al, 2005).…”
Section: Upregulation Of Cfndc5 Expression In Chicken Skeletal Musclesupporting
confidence: 90%
“…Several studies have shown that UCP mRNA expression changes as a function of air temperature (Dridi et al 2008). We observed that, in the liver, high and low FE birds had significantly lower UCP mRNA expression under heat stress.…”
Section: Discussionmentioning
confidence: 66%